2008
DOI: 10.1002/jbm.b.31049
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and local release characteristics of chlorhexidine diacetate loaded within the dental copolymer matrix, ethylene vinyl acetate

Abstract: In vitro results are presented for a novel oral drug-delivery system ultimately intended for treatment of oral infections in immunocompromised patients. Test samples of ethylene vinyl acetate copolymer (EVA) containing chlorhexidine diacetate (CDA) showed desirable antimicrobial properties and steady, slow release into aqueous and other media after an initial burst of drug release in the first day of liquid exposure. By washing away this initial burst, the proposed mouthguard device should be capable of sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 82 publications
(115 reference statements)
0
21
0
Order By: Relevance
“…Ethylene vinyl alcohol (EVAl) copolymer, a polymer consists of hydrophobic ethylene units and hydrophilic vinyl alcohol units, can be obtained by complete hydrolysis of EVA. With good biocompatibility, EVAl has been studied as a matrix material of drug delivery systems over the past few decades (Arnold et al, 2008;Coluccio et al, 2005;Lai et al, 2006;Seki et al, 1989;Shieh et al, 2002;He, 1998, 2000;Yao et al, 2002). Nevertheless, the methods for controlling drug release from drug-loaded EVAl films, such as changing drug loading dose and coating the films with different polymers, cannot allow sufficient variability of drug release.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ethylene vinyl alcohol (EVAl) copolymer, a polymer consists of hydrophobic ethylene units and hydrophilic vinyl alcohol units, can be obtained by complete hydrolysis of EVA. With good biocompatibility, EVAl has been studied as a matrix material of drug delivery systems over the past few decades (Arnold et al, 2008;Coluccio et al, 2005;Lai et al, 2006;Seki et al, 1989;Shieh et al, 2002;He, 1998, 2000;Yao et al, 2002). Nevertheless, the methods for controlling drug release from drug-loaded EVAl films, such as changing drug loading dose and coating the films with different polymers, cannot allow sufficient variability of drug release.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that the release of drugs from EVA films can be regulated by changing the vinyl acetate content (VAc) and drug loading dose (Arnold et al, 2008;Cho et al, 2005;Guo et al, 2007a;Kim and Shin, 2004;Shin and Lee, 2002). Furthermore, adding PEG to EVA films (Fishbein et al, 2001) and coating EVA films with polymer materials (Lesser et al, 1996;Tallury et al, 2007) can effectively increase and decrease the rate of drug release, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…It is usually used for its antiseptic and disinfectant action on wounds, in several products for oral protection and, in general, for dentistry applications (Arnold et al 2008;Fong et al 2010;Hiraishi et al 2008;Huynh et al 2010;Leung et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Arnold et al have observed that CHX-loaded EVA has antimicrobial activity against oral pathogens 38) . CHX is an antimicrobial agent widely accepted as the "gold standard" for oral hygiene 39) .…”
Section: Discussionmentioning
confidence: 99%